Agent based secure intrusion detection and prevention for rushing attacks in clustering MANETs - Aranganathan, A; D. Suriyakala, C (International Journal of Engineering and Technology, 2018)
Intrusion detection is one of challenging issues in wireless networks. The inherently vulnerable characteristics of wireless mobile ad hoc networks make them susceptible to attacks in-spite of some security measures, and it may be too late before any counter action can take effect. As such, there is a need to complement security mechanisms with efficient intrusion detection and response systems. This paper proposes an agent-based model to address the aspect of intrusion detection in cluster based Mobile ad hoc network environment. The model comprises of mobile agents, which are used to detect intrusions, respond to intrusions, mainly preventing the routing attacks while securing them and distributing selected and aggregated intrusion information to all other nodes in the network in an intelligent manner to compensate the attack. The model is simulated to test its operation effectiveness by considering various performance parameters such as, packet delivery ratio, communication overhead, throughput. It implements a secure detection and prevention technique that contains the Blowfish algorithm which is a symmetric encryption and decryption algorithm having a secure standard till date against attacks to make the network transmission secure while monitoring malicious nodes and preventing them from compromising the integrity of the network. Agent based approach facilitates flexible and adaptable security services. Also, it supports component based software engineering components such as maintainability, reachability, reusability, adaptability, and flexibility.Â
Keywords: Mobile Ad hoc network; agent; intrusion detection system; malicious node